A construção social do currículo do curso de história da UFMG: uma análise sobre a criação e implantação das disciplinas de prática de ensino e suas repercussões - Vyasa Puja Peres Teixeira (2011)
This research is focused on the process of creation and implantation of Teaching Practice courses offered by the College of Philosophy and Human Sciences and its repercussions for UFMGs History Department, considering the university context and Brazils political and social atmosphere in relation to curricular changes. We analyzed when, how and why such process took place in the Department. Our goal was to identify the changes occurred in such course since the creation of Teaching Practice courses. Also, we searched to analyze the relation between curricular changes and actions of subjects involved in such reformulations. In this dissertation, we worked with Ivor Goodson (1995) conception of social construction of curriculum, understanding the History course as a social construction. Focused on the social construction of curriculum it was possible to observe the relation between subjects, their interests, strategies and conceptions inside UFMGs History Department. The theoretical- methodological approach adopted by this research was case of study. The unity of analysis or case of this research was the creation and implantation of Teaching Practice courses in the History Department. Data was collected through documental analysis and individual interviews. We reached the conclusion that the movement for curricular reformulations in the History course of UFMG in the last decade, of 2001 and 2009 resulted from disputes and conflicts inside the Department. As Goodson says, as any other social construction, modifications in the curriculum occur in an arena (considered here as the History Department of UFMG) where several interests, conflicts, and power relations take place.